The association between smoking, changes in smoking behavior, and acute pancreatitis: A population‐based cohort study in Korea. Issue 3 (25th November 2022) - Lee, Jae Min; Han, Kyung Do; Lee, Sang Hyub; Park, Jin Myung; Park, Namyoung; Jeon, Hankyu; Kim, Hyun Jin; Ryu, Ji Kon; Kim, Yong‐Tae
Abstract: Background and Aims: In the Asian population, existing studies regarding the association between smoking and acute pancreatitis are few in number. The aim of this study was to investigate the incidence of acute pancreatitis according to smoking habits and smoking habit changes of the Korean population. Methods: We used clinical data from individuals (aged 20 years or older) who received health examinations arranged by the Korean National Health Insurance Service in 2009 ( n = 4 238 822) or in 2009 and 2011 ( n = 2 617 306). The incidence of acute pancreatitis was analyzed according to smoking status or smoking habit change reported by individuals during their health examination. Newly diagnosed acute pancreatitis was identified using claims data from baseline to the date of diagnosis or until December 31, 2018. Results: The risk of acute pancreatitis was significantly higher in current smokers compared with never‐smokers regardless of age or sex. The adjusted hazard ratio (HR) of acute pancreatitis in current smokers increased according to the amount of smoking (HR 1.28; 95% confidence interval [CI], 1.12–1.45 in <10 cigarettes/day, HR 1.4; CI, 1.3–1.52 in 10–19 cigarettes/day, HR 1.66; CI, 1.55–1.78 in ≥20 cigarettes/day). The adjusted HR of acute pancreatitis in continuous smokers was 1.66 (CI, 1.53–1.8) compared with never‐smokers and was higher than smokers who quit smoking (HR 1.34; CI, 1.17–1.54). Conclusions: In this Korean population‐based cohort study, smoking increased the incidence of acute pancreatitis in a dose‐dependent manner, and smoking cessation helped decrease the incidence of acute pancreatitis.